THE UVEITIS – PERIODONTAL DISEASE CONNECTION IN PREGNANCY: CONTROVERSY BETWEEN MYTH AND REALITY - Sutedjo, Widyawati; Prahasanthi, Chiquita; Utomo, Daniel Haryono (Indonesian Journal of Tropical and Infectious Disease, 2012)
Background: Recently, It had been recognized that oral infection, especially periodontal disease are potential contributing factors to a variety of systemic diseases, such as cardiovascular and cerebrovascular diseases, pregnancy problem, diabetes mellitus type 2, etc. However, the adverse effect of periodontal disease toward uveitis still not clearly understood especially if happens during pregnancy. Interestingly, in Indonesia, there is still a myth that pregnant women should not get any dental treatment, therefore, it may deteriorate periodontal disease during pregnancy. Purpose: to explain the possible connection between periodontal disease and uveitis and increasethe awareness of these problems during pregnancy that could be understood by doctor and laymen. Reviews: literatures revealed that dental infection can caused uveitis via metastatic spread of toxin and inflammatory mediators. Additionaly, more recent investigation reported that the neural system may also stimulated by oral infection. In the orofacial regions there's trigeminal nerve complex that also related to the orbital region, thus may also involved in the uveitis pathogenesis. The effects of periodonto pathogens toxins towardimmunocompetent cell and nerves had also been reported by researcher. Moreover, pregnant women are more susceptible to periodontal disease, therefore maintaining oral hygiene and dental monitoring is a mandatory.Conclusion: in woman who susceptible to uveitis, periodontal disease may exacerbate the symptoms especially in pregnancy. Therefore simple explanation about connection of oral infection-systemic diseases especially in pregnancy should be widespread among Indonesian people.